A new fireworm (Amphinomidae) from the Cretaceous of Lebanon identified from three-dimensionally preserved myoanatomy. (December 2015) - Parry, Luke; Wilson, Paul; Sykes, Dan; Edgecombe, Gregory; Vinther, Jakob
Abstract Background Rollinschaeta myoplena gen. et sp. nov is described from the Late Cretaceous (Cenomanian) Konservat-Lagerstätten of Hakel and Hjoula, Lebanon. The myoanatomy of the fossils is preserved in exceptional detail in three dimensions as calcium phosphate, allowing the musculature of the body wall, gut and parapodia to be reconstructed in detail. Results The major muscle groups of polychaetes can be identified inRollinschaeta, including longitudinal muscle bands, circular muscles, oblique muscles, the parapodial muscle complex and the gut musculature, with a resolution sufficient to preserve individual fibres. To allow meaningful comparison with the phosphatized fossil specimens, extant polychaetes were stained with iodine and visualised using microCT.Rollinschaeta myoplena possesses two pairs of dorsal longitudinal muscles, dorsal and ventral circular muscles and a single pair of ventral longitudinal muscles. While six longitudinal muscle bands are known from other polychaete groups, their presence in combination with circular muscles is unique to Amphinomidae, allowing these fossils to be diagnosed to family level based solely on their myoanatomy. The elongate, rectilinear body and equally sized, laterally projecting parapodia ofRollinschaeta are found only within Amphinominae, demonstrating that the Cretaceous species is derived amongst Amphinomida. Conclusion The uniquely preserved myoanatomy ofRollinschaeta has allowed diagnosis of a fossil annelid to subfamily level using microCT as a comparative tool for exploring myoanatomy in fossil and extant polychaetes. Our results demonstrate that fossilized muscles can provide systematically informative anatomical detail and that they should be studied when preserved.